1992
DOI: 10.1002/bjs.1800790625
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic sphincterotomy in young patients with choledochal dilatation and a long common channel: A preliminary report

Abstract: An anomalous elongated pancreaticobiliary common channel encourages reflux up both the biliary tree and the pancreatic ductal system, resulting in progressive choledochal dilatation, cholangitis with ductal calculi, relapsing pancreatitis and malignant change. Transduodenal sphincteroplasty has been used to improve drainage from the abnormal channel. The use of endoscopic sphincterotomy (ES) to establish drainage and minimize the surgical risks is reported in six symptomatic patients with mild choledochal dila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Ng [2] and Terui [7] have speculated that EST was less effective in PBM patients with undilated common channel, however, the sample size was quite small. Thus we performed a further analysis to compare the benefit of EST on patients with undilated common channel and patients with dilated common channel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ng [2] and Terui [7] have speculated that EST was less effective in PBM patients with undilated common channel, however, the sample size was quite small. Thus we performed a further analysis to compare the benefit of EST on patients with undilated common channel and patients with dilated common channel.…”
Section: Discussionmentioning
confidence: 99%
“…Published literature on the use of ERCP in PBM is limited to small series. Ng et al [2] first reported 6 PBM patients who underwent EST, five got satisfactory outcomes. Similarly, Guelrud et al [3] showed that following a mean 26.4 months in 9 PBM patients who underwent ERCP therapy, eight had excellent results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most patients, endoscopic sphincterotomy is probably not indicated, and endoscopic access to the biliary system for removal of stones or sludge is therefore not possible. In selected cases, with fusiform bile duct dilatation and widely dilated common channel, endoscopic sphincterotomy has been attempted, with encouraging results [34]. In patients with Caroli's disease, liver transplantation may be required [35].…”
Section: Treatment Of Choledochal Cystsmentioning
confidence: 99%
“…The intriguing point is that subsequent to our preliminary report on endoscopic treatment for fusiform choledochal cyst in six children 5 years ago, this is the only comprehensive case report using the same approach for the same anomaly [3]. The apparent paucity of contemporary reports may be due to the small number of cases fulfilling the rather stringent selection criteria (including the size of the common bile duct) or to prevailing concerns about the long-term results [3].…”
mentioning
confidence: 99%